Kajian Risiko Bencana Banjir di Kecamatan Bangkala Kabupaten Jeneponto - Ayu Oktavianur; Rumata, Nini Apriani; Emin Praja, Soemitro (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
This research aims to identify the level of flood risk in Bangkala Sub-district, Jeneponto Regency. The analysis method used in identifying the level of flood risk by using disaster risk indicators, including threats, vulnerability and capacity. This analysis is carried out based on factors that affect the level of danger, vulnerability and capacity of the community. Data collection methods were conducted through (1) observation and (2) interviews to obtain data on disaster management capacity, and (3) documentation and interpretation to obtain data related to hazards and vulnerability to flood disasters. The results showed that the risk level is divided into 3 categories, namely low, medium and high. (1) Low category is in Marayoka village, (2) Medium category is in Pallengu, Benteng, Tombo-Tombolo, Jenetallasa, Bontomanai, Gunung Silanu, Kapita and Pallantikang and (3) High category is in Mallasoro, Punagaya Pantai Bahari, Bontorannu and Kalimporo villages. Community synergy together with academics, government and stakeholders is needed to improve community resilience in flood-prone areas.